Enhancing the value-added of traditional herbal medicine through instant product diversification and KUBE Strengthening - Wardani, Arief Kusuma; Apriyanto, Nugraha Dimas; Aji, Adiwira Wahyu; Azizah, Bilqis Rahil; Firdausa, Clara Adinda; Niamah, Nailiz Zulfiatin (Universitas Muhammadiyah Magelang, 2025)
The traditional 'jamu gendong' (herbal medicine) business in Trasan Hamlet, Magelang, faces challenges due to low productivity and an extremely short product shelf life (only one day), which limits the welfare of its practitioners. This community service program aims to transform this traditional business through product innovation and digital market expansion. The methodology employed a participatory approach involving institutional strengthening, product diversification, and digital literacy. The results demonstrated the successful formation of the